(untitled) (Circe de clásicos y modernos, 2022)
This work distinguishes between three types of psychological experience: desires that are stimulated by pleasure; emotions such as anger, gratitude, shame, and also fear, which involve valuations, whether pragmatic or ethical; and despondency or athumia, which is induced by a sense of helplessness and aporia. The first of these is governed by self-control, enkrateia or sôphrosunê, as the corresponding virtue. Emotions are subject to a different psychic mechanism, involving a proper evaluation of the conditions that provoke them. Finally, despondency or athumia constitutes yet another category, as a state of passivity, of loss of agency.